2016
DOI: 10.1016/j.micinf.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells remove cysts of Toxoplasma gondii from the brain mostly by recognizing epitopes commonly expressed by or cross-reactive between type II and type III strains of the parasite

Abstract: Our previous study demonstrated that CD8+ T cells remove cysts of Toxoplasma gondii from the brain through perforin-mediated mechanisms. We here show that a transfer of CD8+ immune T cells primed with a type II or a type III strain of T. gondii both efficiently removed cysts of a type II strain from infected SCID mice, although the former tended to be slightly more efficient than the latter. Similarly, a transfer of type II-primed CD8+ T cells removed cysts of a type III strain. Therefore, CD8+ T cells are cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Moreover, depletion of CD8 but not CD4 T cells impaired the ability of mice to control chronic infection. Both lineages of T cells are required to prevent reactivation in mice chronically infected with an intermediate-virulence type II strain, ME49 (39,54), and CD8 T cells are the primary effector T (T E ) cells responsible for cyst removal in this setting (41,55). Overall, our model, which uses an avirulent type III strain to generate immunological memory, is consistent with the above-mentioned models for chronic infection-and vaccineinduced immunity and positions memory CD8 T cells as central players in host resistance to T. gondii.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, depletion of CD8 but not CD4 T cells impaired the ability of mice to control chronic infection. Both lineages of T cells are required to prevent reactivation in mice chronically infected with an intermediate-virulence type II strain, ME49 (39,54), and CD8 T cells are the primary effector T (T E ) cells responsible for cyst removal in this setting (41,55). Overall, our model, which uses an avirulent type III strain to generate immunological memory, is consistent with the above-mentioned models for chronic infection-and vaccineinduced immunity and positions memory CD8 T cells as central players in host resistance to T. gondii.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas our recent studies demonstrated that CD8 + immune T cells have the capability to remove the cysts from the brains of chronically infected hosts (9, 19), T. gondii antigens recognized by CD8 + T cells for the cyst removal remained unknown. The present study uncovered that GRA6Nt is a key target antigen of the protective T cells to detect the persistent stage of T. gondii for their elimination using a mouse strain genetically resistant to the infection.…”
Section: Discussionmentioning
confidence: 95%
“…2). Our recent study showed that CD8 + immune T cells remove T. gondii cysts mostly by recognizing epitopes commonly expressed in type II and III strains or cross-reactive between these two genotypes (19). Thus, the highly conserved amino acid sequence of GRA6Nt further support the possibility that GRA6Nt is a major target of CD8 + T cells for their anti-cyst protective activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of ICOS, CXCR3, CXCR6, and IL-18R in the brains of T. gondiiinfected SCID mice following a transfer of CD8 ؉ immune T cells compared to a transfer of the normal CD8 ؉ T cells. We previously demonstrated that in contrast to a transfer of CD8 ϩ immune T cells, a transfer of CD8 ϩ normal T cells from uninfected WT mice into infected SCID mice did not reduce the cyst burden in their brains within 1 week after the cell transfer (12,26). Therefore, we examined whether cerebral mRNA levels for ICOS, ICOSL, CXCR3, CXCR6, IL-18R1, and Chil3 differed between the brains of SCID mice following a transfer of CD8 ϩ immune and normal T cells from infected and uninfected WT mice, respectively, as observed between the WT and Prf1 Ϫ/Ϫ CD8 ϩ immune T cells shown in Fig.…”
Section: Resultsmentioning
confidence: 99%